Perceived social support in patients with chronic pain with and without opioid use disorder and role of medication for opioid use disorder. (1st April 2021) - Benville, Julia R.; Compton, Peggy; Giordano, Nicholas A.; Cheatle, Martin D.
Highlights: Social support improves outcomes in chronic non-cancer pain and opioid use disorder. Different opioid use disorder therapies provide different levels of social support. Methadone patients report similar levels of social support as chronic pain patients. Pain patients on buprenorphine report poorer social support than those on methadone. Abstract: Background: A significant predictor of treatment outcomes for patients with chronic non-cancer pain (CNCP) and opioid use disorder (OUD) is the degree and quality of social support they receive. Specifically, in patients with CNCP and on long-term opioid therapy, the development of OUD tends to be associated with losses in social support, while engagement in treatment for OUD improves support networks. Delivery of the evidence-based OUD treatment medications, methadone and buprenorphine, occurs in clinical environments which patently differ with respect to social support resources. The aims of this study were to describe perceived social support in patients with CNCP without OUD (no-OUD), with OUD and on buprenorphine (OUD-BP), and with OUD and on methadone (OUD-methadone). Methods: Using the Duke Social Support Index (DSSI), perceived social support in a sample of Caucasian patients with CNCP and on opioid therapy was compared between no-OUDs (n = 834), OUD-methadone (n = 83) and OUD-BP (n = 99) therapy. Average DSSI scores were compared across groups and a linear regression model computed to describe association between group and perceived social support. Results: No difference was observed in DSSI scores between no-OUDs and OUD-methadone, however scores were lower among OUD-BP participants than those receiving methadone (x = −5.2; 95% CI: −7.5, −2.9) and (x = −6.5, 95% CI: −8.2, −4.9). Conclusions: Patients with CNCP and OUD on methadone therapy endorse levels of social support comparable to those without OUD, however those on buprenorphine therapy report significantly less support, bringing implications for OUD treatment outcomes.